Fluoride release from carbonate-rich fluorapatite during managed aquifer recharge: Model-based development of mitigation strategies. (1st April 2021) - Schafer, David; Sun, Jing; Jamieson, James; Siade, Adam; Atteia, Olivier; Seibert, Simone; Higginson, Simon; Prommer, Henning
Highlights: Managed aquifer recharged with deionised water may cause fluoride mobilisation. Modifications of the treatment process can be used to mitigate the problem. Modifications need to prevent a significant drop in aqueous calcium concentrations. Reactive transport modelling can be used to assess mitigation strategies. Both sea salt and CaCl2 show to be efficient amendments. Abstract: Fluoride-bearing apatite minerals such as fluorapatite (FAP: Ca10 (PO4 )6 F2 ) and related carbonate-rich fluorapatites (CFA: Ca10 (PO4 )5 (CO3, F)F2 ), which occur ubiquitously as trace components of rocks and sediments, may act as sources for geogenic groundwater fluoride contamination. CFA dissolution often occurs in conjunction with declining dissolved calcium concentrations. Therefore, managed aquifer recharge (MAR) operations using deionised or low calcium source water are at risk of disturbing the naturally persisting geochemical equilibrium between CFA and the ambient groundwater and induce fluoride mobilisation. In this study, we employ reactive transport modelling to investigate how an engineered manipulation of the MAR source water composition might mitigate such groundwater fluoride contamination. Based on a previously developed and calibrated model for Australia's largest groundwater replenishment operation, we investigate the efficiency of (i) raising aqueous calcium concentration through the addition of CaCl2 or Ca(OH)2 amendment, (ii) raising aqueous sodium concentrations through the addition of NaCl or sea salt amendment and (iii) raising the pH. The modelling results illustrate in detail how the geochemical zonation around injection boreholes evolves over time and how this affects fluoride release and attenuation for the different amendment types. Treatments involving the addition of calcium and sodium in the source water are both found to be effective at reducing maximum groundwater fluoride concentrations during MAR, with calcium generally producing the greatest reduction in maximum fluoride concentrations. In contrast, increasing the injectate pH was found to be inefficient in reducing fluoride concentrations significantly due to the strong pH buffering effect of the aquifer sediments. Graphical abstract: Image, graphical abstract